Descriptions of larvae of three species of Hydropsyche (Trichoptera, Hydropsychidae) from China - Xu, Ji-Hua; Sun, Chang-Hai; Wang, Bei-Xin (Zootaxa, 2018)
Twenty-one individuals of Hydropsyche from An-hui and Zhe-jiang Provinces, China, were examined and their DNA barcode sequences were generated and analyzed. The larvae and males of H. arion, H. columnata, H. simulata, and H. trifora were associated by mtCOI gene sequences. The larvae of H. arion, H. columnata, and H. trifora are described in detail and their diagnostic photographs are provided. Character photographs of the H. simulata larva are also presented. A key to 5th instar larvae of 15 species of Chinese Hydropsyche is provided.